Germinação e alterações fisiológicas em sementes de chia (Salvia hispanica L.) sob condições abióticas - Paiva, Emanoela Pereira de (2017)
Chia (Salvia hispanica L.) is a species that presents considerable economic importance because it is being used as functional foods and by the pharmaceutical industry. The standardization of the germination test of a particular species in the Laboratories of Seeds Analysis, as well as knowing the factors that influence its process, has fundamental importance in the definition of the responses of the species to the intrinsic and extrinsic factors to the seed. In this sense, four experiments with chia seeds were carried out, aiming to determine the appropriate procedures for conducting the germination test and to verify the effects of water and saline stress on the germination and initial development of the seedlings of this species under different temperatures. The experiments were conducted in the Laboratory of Seed Analysis (LAS) of the Federal Rural Semi-Arid University (UFERSA, Mossoró Campus–RN). The statistical design was completely randomized, with four replications. In the first experiment, the influence of two substrates and six levels of wetting on the germination of chia seeds was evaluated. For this, the paper towel substrates (Germitest®) and blotting paper and six volumes of water (1.5; 2.0; 2.5; 3.0; 3.5; 4.0) were multiplied by the dried substrate‟s mass. For the second experiment, the effects of different light regimes and temperatures under the germination of S. hispanica seeds were evaluated using three conditions of light (constant light, dark constant and light / dark alternation with 8 hours of light And 16 h dark) and six temperatures (20; 25; 30; 35; 20-30 and 25-30 °C). In the third experiment, the saline concentrations evaluated were 0.0 (control); 4.5; 9.0; 13.5 and 18.0 dS m-1 and four temperatures: 20, 25, 30 and 20-30 °C. In the fourth experiment, five levels of polyethylene glycol (PEG 6000) (0.0; -0.1; -0.2; -0.3; -0.4 MPa) and four temperatures (20, 25, 30, 20-30 °C). In all the experiments, the germination, vigor and biochemical tests of seedlings were evaluated. The S. hispanica seed germination test should be conducted on the blotting substrate (on paper) with the amount of water between 2.5 and 4.0 times the weight of the dry substrate. The seeds germinated in the blotter paper obtained greater germination growth and accumulation of dry matter of the S. hispanica seedlings in relation to the germinated seedlings in the Germitest® towel paper. The S. hispanica seed germination test can be conducted at constant temperatures of 25 °C and alternating 25-30 °C. The germination of the seeds of S. hispanica is indifferent to the luminosity (neutral photoblastic), however, the greatest growth and accumulation of dry mass occur in the presence of light. Salinity levels greater than 4.5 dS m-1 associated with temperatures of 30 or 20-30 °C affect negatively germination, vigor, growth and biochemical components of seedlings. The temperature of 25 °C provides the best conditions for the development of S. hispanica seedlings. The level of polyethylene glycol of -0.4 MPa for all temperatures studied, and -0.3 MPa at temperatures of 30 °C and 20-30 °C made the germination and vigor of S. hispanica seedlings unfeasible. The S. hispanica seedlings are able to perform osmotic adjustment under water stress conditions up to -0.3MPa when coming from germinated seeds at temperatures up to 25ºC